Airway Epithelium Interactions with Aeroallergens: Role of Secreted Cytokines and Chemokines in Innate Immunity - Gandhi, Vivek D.; Vliagoftis, Harissios (Frontiers in Immunology, 2015)
Airway epithelial cells are the first line of defense against the constituents of the inhaled air, which include allergens, pathogens, pollutants and toxic compounds. The epithelium not only prevents the penetration of these foreign substances into the interstitium, but also senses their presence and informs the organism’s immune system of the impending assault. Epithelium accomplishes the latter through the release of inflammatory cytokines and chemokines that recruit and activate innate immune cells at the site of assault. These epithelial responses aim to eliminate the inhaled foreign substances and minimize their detrimental effects to the organism. Quite frequently, however, these innate immune responses of the epithelium to inhaled substances may become self-damaging because of chronic and high level release of pro-inflammatory mediators. The interactions of airway epithelial cells with allergens will be discussed with particular focus in the interactions-mediated epithelial release of cytokines-chemokines and their role in the immune response. As pollutants are other major constituents of inhaled air, we will also discuss how pollutants may alter the responses of airway epithelial cells to allergens.